SUN-175 Severe Lactic Acidosis Due to Intentional Suicide Attempt with Metformin and Its ICU Management - Motazedi, Banafsheh (J Endocr Soc, 2019)
Background: Metformin is a biguanide used in treatment of Type 2 Diabetes Mellitus. Deliberate suicide attempt with Metformin is rare and manifests as severe lactic acidosis with mortality rate of 30%. Clinical Case: A 58-year old male with Type 2 Diabetes Mellitus was brought to the Emergency Department (ED) after intentional overdose with 30 grams of Metformin. Upon arrival to the ED, he was semiconscious and confused. His BP: 99/54 mmHg, HR: 88 bpm, RR: 18, Temp: 98.2°F, and saturating 100% on ambient air. Blood chemistry panel revealed Creatinine of 3.14 mg/dL (n: 0.6-1.30 mg/dL), anion gap of 26 mEq/L (n: 8-12 mEq/L), lactic acid of 19.8 mmol/L (n: 0.8-2.1 mmol/L), and blood glucose of 198 mg/dL (n: 74-106 mg/dL). Urine drug screen, serum salicylate, acetaminophen, alcohol, Methanol, and Ethelyn Glycol levels were negative. Metformin concentration was later found to be 41 mcg/ml (n: 0.10 mcg/ml). He received activated charcoal in the ED and ICU was urgently consulted. Patient ultimately developed acute respiratory failure due to severe acidosis (ABG; pH: 6.97 (n: 7.35-7.45), pCO2: 27 mmHg (n: 35-48 mmHg), and HCO3: 6.2 mEq/L (n: 18-23 mEq/L)). He was intubated for airway support and was placed on mechanical ventilation. Due to persistent hypotension, he was started on pressor support with Phenylephrine as well as continuous infusion of sodium bicarbonate 8.4% at 200 ml/hr. Patient’s blood glucose dropped to as low as 22 mg/dL (n: 74-106 mg/dL) and thus he was started on intravenous infusion of Dextrose 5% Normal Saline at 100 ml/hr to avoid life threatening hypoglycemic coma. Nephrology was consulted for emergent dialysis. Patient’s condition quickly deteriorated due to severe lactic acidosis thus requiring two additional pressor support with infusion of Norepinephrine and Vasopressin as well as addition of Hydrocortisone and oral Midodrine. His renal function worsened, and he became oliguric. Patient subsequently received intermittent hemofiltration for 2 consecutive days for duration of 3 hours and 8 hours, respectively. After initiation of hemofiltration, patient’s condition gradually improved, his blood pressure stabilized, his creatinine & lactic acid levels normalized, and he was successfully extubated. He made a full recovery and was safely discharged home after 13 days of hospitalization. His Metformin level on discharge was 0.10 mcg/ml (n: 0.10 mcg/ml). Patient has been followed closely at our out-patient clinic since discharge and remains in good health. Conclusion: Metformin overdose/toxicity is a serious condition associated with significant mortality and should be considered in diabetic patients presenting with severe lactic and metabolic acidosis. Our recommendations for management of Metformin associated lactic acidosis includes; timely recognition, decontamination, ICU admission and emergent hemodialysis for correction of severe metabolic abnormalities.